Examining the Aspects Decrease the Development of the Small and Medium Enterprises in Al Batinah Province - Oman - Al Farsi, Kholood; Alattar, Nebras (Applied computing Journal, 2021)
Small and medium-sized enterprises (SMEs) play an important role in any developing economy. In Oman, about 60% of SMEs are the source of employment. There is an increase in SMEs, but there are also challenges linked with growth; this research project explores the specific challenges faced by small and medium business owners. This study used a simple random sample with data from 200 SME owners, and data was collected using a well-design questionnaire. The data was analyzed in more detail by descriptive statistics and ANOVA statistics. A reliability test was performed to determine how reliable the data collecting instrument was. The limitations of this work and several suggestions are recorded. Several hypotheses are tested, and the results show a significant relationship between Financial management constraints and SME growth. And, also, there is a significant relationship between Marketing management constraints and the growth of SMEs. And, also, there is no significant relationship between the relationship of statistical importance between the Human resource constraints and the growth of SMEs in Oman.